3WD omni-wheeled mobile robot using ARM processor for line following application - Ayob, Mohammad Afif (2011)
Performance efficient processors have become increasingly important for mobile robots with numerous actuators and sensors. Therefore, this project is to implement a 32-bit low-power ARM processor into the development of a 3WD omni-directional mobile robot equipped with IR sensor capabilities. The scope of the project is narrowed down to the usage of Embedded Artists’ LPC2148 USB QuickStart Board, digital fiber sensor, DC brushless motor, and omni-wheel. Most of the tools and necessary equipment for the project development can be obtained within the UTHM. At the end of this project, the ARM processor has successfully generate the desired PWM for motor control and respond to the digital input from the interface of IR sensor to the microcontroller.